Sensitivity of newly transplanted coffee plants to climatic conditions at altitudes of Minas Gerais, Brazil - Aparecido, Lucas Eduardo de Oliveira [UNESP]; Rolim, Glauco de Souza [UNESP]; de Souza, Paulo Sergio (My University, 2015)
The influence of climate on the early development of newly transplanted coffee plants is poorly known. Good initial development is important for the sustainability of longevity and yield. We determined the climatic sensitivity of five-month-old coffee seedlings transplanted under climatic conditions at high altitude during the first two years of development in the state of Minas Gerais in Brazil. Plant height (PLH), orthotropic stem diameter (SDI), and plagiotropic branch number (PBN) were recorded every three months, and the effects of the climatic variables degree days (DD), potential evapotranspiration (PET), actual evapotranspiration (AET), global radiation (Qg), and water deficit (WD) rate in conventionally tilled, furrowed, and untilled systems were determined. The data were analysed with sigmoidal and peak models adjusted by least squares fitting. The development of the coffee crop was sensitive to the climatic conditions. Plant height, stem diameter, and plagiotropic branch number were logistic functions of DD, PET, AET, and Qg and had a parabolic relationship with WD. The coffee plants transplanted in the untilled system had larger SDIs and higher PBNs. The furrowed system produced the tallest plants. Water deficit was the most important meteorological variable during the study period. Water deficits of 0.5-0.7 mm d-1 promoted the development of PLH, SDI, and PBN by 0.19 cm d-1, 0.06 cm d-1 and 0.10 d-1, respectively.
Keywords: Agrometeorological modelling; Multivariate analysis, growth analysis; Water budget